1988
DOI: 10.1346/ccmn.1988.0360601
|View full text |Cite
|
Sign up to set email alerts
|

Stacking Order in a 14.30-Å Mg-Vermiculite

Abstract: Abstract--The stacking order ofa 14.30-/~ Mg-vermiculite from Santa-Olalla, Spain, has been determined from Weissenberg photographs. The results prove that the Mg-vermiculite structure is not a 2-layer polytype structure, but a semi-ordered one. Because the structure is semi-ordered, its resolution needed a dual approach: (1) a direct approach using an electron density projection along the y axis in conjunction with a one-dimensional electron-density projection onto the z axis; and (2) an indirect approach in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The CEC varies between the 120 and 200 cmol+/kg (air dried vermiculites) or 140 and 240 cmol(+)/kg (dehydrated vermiculites) [14,15]. Water molecules associated with internal surfaces evokes hydration of interlayer cations.…”
Section: Layer Charge (X) Per Half Unit Cellmentioning
confidence: 99%
See 3 more Smart Citations
“…The CEC varies between the 120 and 200 cmol+/kg (air dried vermiculites) or 140 and 240 cmol(+)/kg (dehydrated vermiculites) [14,15]. Water molecules associated with internal surfaces evokes hydration of interlayer cations.…”
Section: Layer Charge (X) Per Half Unit Cellmentioning
confidence: 99%
“…The hydration properties are controlled by the interlayer cations Mg 2+ and minor amounts of Ca 2+ , Na + , and K + . The cation radius and charge influence the degree of hydration state in the interlayer and the stacking layer sequences [9,15,19,22,28]. The hydration state of vermiculite was defined by the number of water layers in the interlayer space.…”
Section: Layer Charge (X) Per Half Unit Cellmentioning
confidence: 99%
See 2 more Smart Citations
“…Annabi-Bergaya et al (1980) and Ben Rhaiem et al (1987) observed a similar phenomenon in low-charge Na-smectite. Studies in which either vermiculite or Ca-smectite was used (e.g., Ben R h~e m et al, 1987;de la Calle et al, 1976de la Calle et al, , 1988 would have failed to show an appreciable effect of either methanol or ethanol, because the layers would already have been largely collapsed due to other forces (e.g., presence of divalent cations), leaving the possibility for only a minor influence from the low-dielectric solvents.…”
Section: Clay Panicle Arrangementsmentioning
confidence: 99%